Implementing interventions to promote spectacle wearing among children with refractive errors: A systematic review and meta-analysis - Wu, Linrong; Feng, Jiayi; Zhang, Mingzhi (Frontiers in Public Health, 2023)
Purpose:To study the compliance of Children with refractive errors to provide free spectacles, and the reason for not wear. Methods:We systematically searched PubMed, EMBASE, CINAHL, Web of Science, Cochrane Library databases from their inception to April 2022, We included studies published in English. The search terms were-("randomized controlled trial"[Publication Type] OR "randomized"[Title/Abstract] OR "placebo"[Title/Abstract]) AND (("Refractive Errors"[MeSH Terms] OR ("error refractive"[Title/Abstract] OR "errors refractive"[Title/Abstract] OR "refractive error"[Title/Abstract] OR "refractive disorders"[Title/Abstract] OR "disorder refractive"[Title/Abstract] OR "disorders refractive"[Title/Abstract] OR "refractive disorder"[Title/Abstract] OR "Ametropia"[Title/Abstract] OR "Ametropias"[Title/Abstract])) AND ("Eyeglasses"[MeSH Terms] OR ("Spectacles"[Title/Abstract] OR "Glasses"[Title/Abstract]) AND ("Adolescent"[MeSH Terms] OR ("Adolescents"[Title/Abstract] OR "Adolescence"[Title/Abstract]) OR "Child"[MeSH Terms] OR "Children"[Title/Abstract])). All the studies were required to be randomized controlled trials. Two researchers independently searched the databases and initial screening obtained 64 articles. Two reviewers assessed data quality independently. Results: 14 articles were eligible for inclusion and meta-analysis included 11 studies. The overall compliance with spectacle use was 51.19%. There was statistical significance in the effect of free spectacle on children spectacle-wear compliance (OR=2.45; 95%CI=1.39-4.30). In the subgroup analysis, longer follow-up time was associate with significantly smaller reported ORs. Most studies have concluded that sociomorphic factors, RE severity, and other factors contribute to children not wearing glasses at the end of follow-up. Conclusion: The high compliance of free spectacles combined with educational interventions, suggested that policy implementation may be recommended to integrate free spectacles with other measures such as educational interventions together. In addition, A combination of additional health promotion strategies may be needed to improve the acceptability of refractive services and eyewear use.